PATRONAGE INSTALLATION IN FOREST AND LAND FIRE IN RIAU PROVINCE (STUDY ON LAW ENFORCEMENT WITH CORPORATE ACTORS) - Harun, Hariwiyawan; Bratasena, I Gede Nyoman; Riyadi, Sugeng (International Review of Humanities Studies, 2021)
This study intends to uncover, analyze and evaluate law enforcement practices against criminal acts of forest and land fires with corporate actors in the Riau Police. Riau was chosen as the research location because the phenomenon of forest and land fires in Riau was so complex. The impact caused by forest and land fires in Riau is not only a domestic problem, but also concerns regional areas, especially Singapore and Malaysia. The research is focused not on law enforcement of forest and land fires, but rather on the relationship of patronage and policing in handling forest and land fires in Riau Province. Patronage politics between the police and corporations from the plantation and industrial plantation sectors. In this context, dialectics (habitus, arena, capital) and patronage networks will be deepened, which then influence policing actions in law enforcement carried out by the police.